2018
DOI: 10.1007/s40273-018-0642-5
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Studies Comparing the Measurement Properties of the Three-Level and Five-Level Versions of the EQ-5D

Abstract: BackgroundSince the introduction of the five-level version of the EQ-5D (5L), many studies have comparatively investigated the measurement properties of the original three-level version (3L) with the 5L version.ObjectiveThe aim of this study was to consolidate the available evidence on the performance of both instruments.MethodsA systematic literature search of studies in the English and German languages was conducted (2007–January 2018) using the PubMed, EMBASE, and PsycINFO (EBSCO) databases, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
209
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 227 publications
(242 citation statements)
references
References 63 publications
29
209
2
2
Order By: Relevance
“…We also examined the informational characteristics of the competing descriptive systems by using measures frequently reported in the literature, such as Shannon's absolute and relative measures of informativity. Our findings were similar to the summaries reported by Buchholz et al [3], with zero or modest improvements in relative informativity in the general population but gains in absolute informativity across all domains. However, for a multimorbid population, there was an improvement in both absolute and relative measures of informativity across most domains.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We also examined the informational characteristics of the competing descriptive systems by using measures frequently reported in the literature, such as Shannon's absolute and relative measures of informativity. Our findings were similar to the summaries reported by Buchholz et al [3], with zero or modest improvements in relative informativity in the general population but gains in absolute informativity across all domains. However, for a multimorbid population, there was an improvement in both absolute and relative measures of informativity across most domains.…”
Section: Discussionsupporting
confidence: 91%
“…A key problem for the EQ-5D-3L is its tendency to generate significant 'ceiling effects' whereby a high proportion of respondents report having 'no problems' on all or one domain [3]. In line with previous studies using general population samples, we found a 10.6 percentage point fall in full health (no problems on all domains) reported for the EQ-5D-5L versus the EQ-5D-3L [5,20,21].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations